The Effect of Using Problem Based Learning Model on Critical Thinking Ability with Moderator Variable of Learning Motivation - Nurhayati Nurhayati; Pupu Saeful Rahmat; Yeyen Suryani (Green Publisher Indonesia, 2024)
The ability of critical thinking is a skill in depth and logic with various scientific activities for making decisions. This research aims to determine the differences in critical thinking ability of students who receive problem based learning model and students who receive lecture method; differences in critical thinking ability of experimental class students who have low, medium and high learning motivation; and the effect of interaction between using problem based learning model and learning motivation on critical thinking ability of class VIII students in Social Sciences Subjects at Kalimanggis 2 State Junior High School. The research method used was a quasi-experimental method with a factorial design. The research subjects were 48 students of class VIII of Kalimanggis 2 State Junior High School, divided into class VIII.A (experiment) and class VIII.B (control), each with 24 people. Data collection techniques used field research with instruments in the form of tests and questionnaires. Hypothesis testing used two-way analysis of variance. Based on the research results, it can be seen that there were differences in critical thinking ability of students who received problem based learning model and students who received lecture method; there were differences in the critical thinking ability of students in experimental class who had low, medium and high learning motivation; and there was an interaction between the use of problem based learning model and learning motivation on critical thinking ability of class VIII students in Social Sciences Subjects at Kalimanggis 2 State Junior High School.